KARAKTERISTIK CAIRAN BIANG YANG DIBUAT DARI CHIPS UBI KAYU, PARUTAN UBI KAYU DAN LIMBAH CAIR TAPIOKA - Sri Budi Wahjungsih; Bambang Kunarto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2012)
The process of mokal flour naturally still takes a relatively long time because the fermentation process lasts for 3 days. Therefore necessary to find a more effective and efficient solution to shorten the fermentation process. This study aimed to investigate the characteristics of the inoculum liquids based on some sources namely cassava chips liquid, cassava crushed liquid and tapioca liquid waste can accelerate fermentation mokal. The design of experiments using a completely randomized design (CRD) one factor, with 3 kinds of inoculum liquid sources as treatmants and 3 replicatations. The treatment sources are made from Markonah cassava variety, that named with cassava chips liquids (B1) cassava crused liquid (B2) and tapioca liquid waste. Duncan multiple range test (5%) used to compare the different of treatmen. The results showed the liquid source can be obtained from three sources, with good characteristics and the used of inoculm liquids on mokal fermentation process can accelerate the fermentation process from 3 days to 24 hours. The inoculum liquid can be saved on room temperature for 4 days and cold storage for 6 days